2018
DOI: 10.3889/oamjms.2018.115
|View full text |Cite
|
Sign up to set email alerts
|

Rathke's Cleft Cyst or Pituitary Apoplexy: A Case Report and Literature Review

Abstract: BACKGROUND:During the examination of the sellar region by magnetic resonance imaging, hyperintensity in T1 weighted is a common finding. This signal intensity has different sources, and its significance depends on the clinical context. Pathologic variations in T1 signal hyperintensity may be related to clotting of blood (pituitary apoplexy) or the presence of a high concentration of protein (Rathke cleft cyst). The purpose of this study is to describe the significance of intracystic nodule, a diagnostic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…First, MRI strongly indicated that the intrasellar component of the lesion was etiologically associated with the pituitary gland. Second, the features of the lesion appeared similar to those of RCCs described in human (3234) and veterinary (31) medicine. In addition, although we performed cytological analysis only after the surgery (which involved removal of the hypophysis), the findings did not exclude a neuroendocrine origin.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…First, MRI strongly indicated that the intrasellar component of the lesion was etiologically associated with the pituitary gland. Second, the features of the lesion appeared similar to those of RCCs described in human (3234) and veterinary (31) medicine. In addition, although we performed cytological analysis only after the surgery (which involved removal of the hypophysis), the findings did not exclude a neuroendocrine origin.…”
Section: Discussionsupporting
confidence: 62%
“…Current literature pertaining to veterinary medicine does not document any cases involving such lesions in dogs, although one study has described Rathke's cleft cyst (RCC) secreting antidiuretic hormone in a cat (31). In human medicine, RCCs are benign lesions that arise within the sella, between the anterior and posterior lobes of the pituitary gland, and can compress the surrounding structures of the sella turcica (optic chiasm and pituitary gland); RCCs are incidentally detected in 4–33% human autopsies (32). T2W and T1W images show heterogeneous signal intensity and hyperintensity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…La alteración de este proceso genera acumulación de secreciones mucoides causando dilatación quística. 6 Los quistes de la hendidura de Rathke por lo regular cursan asintomáticos y se encuentran como hallazgo incidental o bien en autopsias de adultos hasta en un 11-22%. 3 Los que originan síntomas son la minoría y están en relación directa con el tamaño de la lesión y su extensión supraselar, dado que al adquirir un tamaño considerable comprimen las estructuras adyacentes y causan manifestaciones que en los adultos suelen ser cefaleas frontales episódicas presentes en 44-81% de los casos sintomáticos y disfunción hipofisaria encontrada en 30-60% de los pacientes.…”
Section: N T Ro D U C C I ó N D I S C U S I ó N P R E S E N Tac I ó N D E L Ca S Ounclassified
“…9 Otra presentación poco común es la apoplejía pituitaria, la cual se caracteriza por un cuadro clínico consistente en cefalea, cambios en la agudeza visual, vómito, oftalmoplejía y alteración del estado de conciencia. 6 Por último la meningitis aséptica se presenta con signos de irritación meníngea y la punción lumbar revela líquido de características inflamatorias. 7 La resonancia magnética (RM) es la imagen de elección para el diagnóstico siendo superior a la tomografía axial computarizada (TAC), determinando de manera más precisa la extensión del quiste y su relación con la arteria carótida interna y los senos cavernosos, además de una mayor resolución de contraste.…”
Section: N T Ro D U C C I ó N D I S C U S I ó N P R E S E N Tac I ó N D E L Ca S Ounclassified
“…8,9 Although most are asymptomatic, they can cause mass effect, leading to headaches, pituitary dysfunction, or visual disturbance. 10 Treatment for large or symptomatic cysts almost invariably involves surgical resection to evacuate the cyst and epithelium, typically via a transsphenoidal approach. 11 Small, asymptomatic lesions can be followed radiographically.…”
mentioning
confidence: 99%